(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study describes the current state of medication adherence and identifies related factors among outpatients with type 2 diabetes at Nam Dinh General Hospital in 2025. Methods: This study describes the current state of medication adherence and identifies related factors among outpatients with type 2 diabetes at Nam Dinh General Hospital in 2025. Results: The proportion of male patients was higher than female patients, at 60.2%/39.8%; 45.9% of patients admitted to occasionally forgetting to take their medication, and 55.6% had forgotten to take their medication in the past two weeks. 29.6% of patients had reduced their dosage or stopped taking their medication when they felt unwell; 12.2% of patients had forgotten to bring their medication when traveling; 10.2% of patients found the long-term treatment inconvenient, and all patients found it difficult to remember all their medications to varying degrees. Conclusion: The classification of medication adherence levels among diabetic patients at Nam Dinh General Hospital shows that 35.7% of patients have high adherence, 41.8% have moderate adherence, and 22.5% have low adherence. Age, gender, and source of information are related to the level of adherence.